Antykościelne prawodawstwo w Polsce 1945–1956 - Romański, Mirosław (Przegląd Prawno-Ekonomiczny, 2013)
Streszczenie dostępne wyłącznie w języku angielskim: Article titled Anti-Church/Religious Legislation in Poland 1945–1956 elaborates the most important legal acts issued by the communist authorities in the intensive witch-hunt against Catholic Church of the Stalinist period. The author presented the wide scale of authorities actions and the diversity of legal acts which were issued. They were supposed to guarantee the communists the authorities interference both in the internal policy of the Church and its role and position in the social life. That kind of policy was run with determination, and its basic aim was to deprive the Church all public rights, its incapacitation and making conditional on decisions made by the state authorities, not respecting its position from the moment of II world war ending. The declared aims, in spite of issuing lots of anti-church legal acts, had not been achieved by Communists fully. The Catholic Church did not surrender to common discrimination from the state authorities and was a serious counterbalance to initiatives taken by the communist authority apparatus.